The impact of imposing processing strategies on L2 learners' deliberate study of lexical phrases. (February 2016) - Eyckmans, June; Boers, Frank; Lindstromberg, Seth
Abstract: Lexical phrases (e.g., collocations and idioms) have in recent years attracted a fair amount of interest in the fields of SLA and language pedagogy. However, there is still a shortage of empirical studies of instructional methods and techniques. The present study focuses on the deliberate memorization of L2 phrases and tests the effectiveness of two proposals for how to help learners accurately recall the lexical composition of L2 phrases. EFL learners ( N = 65) studied a list of 32 figurativeverb + noun-phrase expressions (e.g., turn the tide ) glossed in L1. In one condition, they were only instructed to study the list. In a second, they were additionally instructed to identify phrases whose verb is non-congruent with the L1 translation. In a third, the instruction was to identify phrases that alliterate. The 32 phrases included roughly equal numbers of congruent and alliterative ones. It was hypothesized that the extra instructions would cause learners to pay closer attention to the verbs in the phrases and that this would result in better recall. Comparisons of pre- to post-test gains suggest that the instruction to look out for alliteration enhances retention, whereas the instruction to compare with L1 does not.